Dietary inclusion of blanched African bread fruit (Treculia africana) pulp on the growth performance, haematological indices and nutrient digestibility in Weaner rabbits - Ugwu, C. M.; Ani, A. O.; Ogwuegbu, M. C.; Anizoba, N. W.; Ezenwosu, C.; Onu, E. A.; Nwoga, C. C.; Ali, L. C. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
Current study examined the impact of blanched African bread fruit pulp (BABP) on growth per-formance, haematology and nutrient digestibility of Weaner rabbits. A total of 200 60-day-old New Zealand White Weaner rabbits with an average weight of 759.5 g were randomly assigned to five groups and fed 0% (control), 5, 10, 15 and 20 % blanched African bread fruit pulp in a completely ran-domized design. The trial lasted for 7 d of adaptation and 56 d for testing. Growth performance was recorded from 60 to 116 d of age (n=5 per treatment with 40 rabbits, 10 per replicate), haematological indices at 116 d of age and nutrient digestibility from 112 to 116 d of age were determined (n=5 per treatment with 16 rabbits, 4 per replicate). Results showed that dietary BABP supplementation at 15, and 20% decreased (P < 0.05) the feed intake and body weight gain. The digestibility of crude protein, crude fiber, and ether extract were also decreased (P < 0.05). Moreover, rabbit at 15, and 20% showed decreased (P < 0.05) packed cell volume, white blood cell and haemoglobin concentration. It was con-cluded that BABP can be incorporated into rabbit diets up to 5-10% inclusion level, without negatively affecting growth performance, haematological indices and nutrient digestibility of rabbits.